2009
DOI: 10.1111/j.1365-2249.2009.03901.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic isolation of CD4+CD25+FoxP3+ natural T regulatory lymphocytes for clinical applications

Abstract: Summary Although CD4+ /CD25 + T regulatory cells (Tregs) are a potentially powerful tool in bone marrow transplantation, a prerequisite for clinical use is a cellseparation strategy complying with good manufacturing practice guidelines. We isolated Tregs from standard leukapheresis products using double-negative selection (anti-CD8 and anti-CD19 monoclonal antibodies) followed by positive selection (anti-CD25 monoclonal antibody + and CD4 + /CD25 -reacting clones which are potentially responsible for triggerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…94, 95 Cells originating from both the PB and LNs were regulatory in nature, suggesting the presence of Treg cells in both of these compartments of the canine peripheral immune system. Further studies will be required to explore the mechanistic basis of suppression mediated by canine CD4 + CD25 high FOXP3 high Treg cells, but this work and a recently published paper using a canine-specific anti-CD25 mAb 55 provide the first direct evidence of Treg cells in dogs and represent an important advance in this field.…”
Section: Discussionmentioning
confidence: 97%
“…94, 95 Cells originating from both the PB and LNs were regulatory in nature, suggesting the presence of Treg cells in both of these compartments of the canine peripheral immune system. Further studies will be required to explore the mechanistic basis of suppression mediated by canine CD4 + CD25 high FOXP3 high Treg cells, but this work and a recently published paper using a canine-specific anti-CD25 mAb 55 provide the first direct evidence of Treg cells in dogs and represent an important advance in this field.…”
Section: Discussionmentioning
confidence: 97%
“…10 The main obstacle to clinical application of human Tregs is their paucity in the peripheral blood. Although ex vivo-expanded polyclonal 11 or recipient-specific Tregs 12 were proposed to circumvent this potential barrier, we opted for closed, automated immunoselection 13 of naturally occurring Tregs. In the present study, for the first time in humans, we show that the early infusion of freshly isolated donor Tregs followed by Tcons at the time of full-haplotypemismatched HSCT prevented GVHD while favoring Tconmediated posttransplantation immune reconstitution.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a pioneer experience of the Perugia group has clearly demonstrated that naturally occurring Tregs harvested from healthy donors efficiently control the alloreactivity of a large number of otherwise lethal, conventional T cells 7173. Using this strategy, there was a rapid, sustained increase in peripheral blood T-cell subpopulations.…”
Section: Post-transplant Immunological Reconstitution and Infectionsmentioning
confidence: 99%